Implementation of online learning and its impact on student science competency - Muhammad Syazali; Mohammad Liwa Ilhamdi (Jurnal Pijar Mipa, 2022)
Student science learning outcomes in the first year of online learning are good. However, this is in the Basic Science course, whose learning objectives do not cover all science topics and are at the basic science level. Continuous monitoring of student performance during online learning is also a necessity. This study analyzes student science learning outcomes in Science Education courses in the second year of online learning implementation. This research is a type of descriptive research that uses qualitative methods. The sample consists of 147 Elemntary School Teacher Department (PGSD) FKIP students at the University of Mataram who had taken Science Education courses. The learning outcomes data collected are final grades in qualitative – A, B+, B, C+, C, D+, D, or E. This data is collected using a closed questionnaire instrument via google forms. The data were analyzed quantitatively using descriptive statistics. The study results provide information that students can be grouped into three based on their scientific competence. This group is students with excellent, good, and sufficient competence. Most of them (98.6%) have competence in the good and very good category.